Density Functional Theory Calculations on Oxidative CC Bond Cleavage and NO Bond Formation of [RuII(bpy)2(diamine)]2+ via Reactive Ruthenium Imide Intermediates. Issue 46 (29th September 2014) - Guan, Xiangguo; Law, Siu‐Man; Tse, Chun‐Wai; Huang, Jie‐Sheng; Che, Chi‐Ming
Abstract DFT calculations are performed on [RuII(bpy)2(tmen)]2+ (M1, tmen=2, 3‐dimethyl‐2, 3‐butanediamine) and [RuII(bpy)2(heda)]2+ (M2, heda=2, 5‐dimethyl‐2, 5‐hexanediamine), and on the oxidation reactions of M1 to give the CC bond cleavage product [RuII(bpy)2(NH=CMe2)2]2+ (M3) and the NO bond formation product [RuII(bpy)2(ONCMe2CMe2NO)]2+ (M4). The calculated geometrical parameters and oxidation potentials are in good agreement with the experimental data. As revealed by the DFT calculations, [RuII(bpy)2(tmen)]2+ (M1) can undergo oxidative deprotonation to generate Ru‐bis(imide) [Ru(bpy)2(tmen‐4 H)]+ (A) or Ru‐imide/amide [Ru(bpy)2(tmen‐3 H)]2+ (A′) intermediates. Both A and A′ are prone to CC bond cleavage, with low reaction barriers (ΔG≠) of 6.8 and 2.9 kcal mol−1 for their doublet spin states 2A and 2A′, respectively. The calculated reaction barrier for the nucleophilic attack of water molecules on 2A′ is relatively high (14.2 kcal mol−1). These calculation results are in agreement with the formation of the RuII‐bis(imine) complex M3 from the electrochemical oxidation of M1 in aqueous solution. The oxidation of M1 with CeIV in aqueous solution to afford the RuII‐dinitrosoalkane complex M4 is proposed to proceed by attack of the cerium oxidant on the ruthenium imide intermediate. The findings of ESI‐MS experiments are consistent with the generation of a ruthenium imide intermediate in the course of the oxidation.